Blood volumes in pediatric clinical trials: a review of current regulations and guidance for research studies. (November 2014) - Veal, Gareth J
Significant progress is being made in advancing the development of clinical research in pediatrics. In continuing this trend, we must safeguard the interests and welfare of children participating in increasingly expansive and complex clinical trials designed to maximize clinical and scientific outputs. The potential impact of taking multiple blood samples and sometimes substantial blood volumes from children is at present unclear. Available guidelines define safe limits of 1–5% total blood volume, but these guidelines vary and are not evidence-based. The current review looks at the basis for these guidelines, summarizes previously published studies directly addressing this important issue and discusses factors that should be considered in the design and implementation of clinical research involving blood sampling in children.